A High Power Low-Cost Balancing System for Battery Strings. (February 2019) - Xu, Jun; Mei, Xuesong; Wang, Junping
Abstract: Cell imbalance is one of the most critical problems in battery storage systems, especially in series-connected battery strings. The passive balancing methods are widely used in real applications, for their low cost, low computation complexity and easy to implement. However, the balancing current is still very small for commercial passive balancing systems and even the bleeder resistances are small enough, it suffers the problem that the balancing current cannot be tuned as wish. To address this problem, this paper proposed a high power low-cost balancing system, in which the bleeder resistors are removed from the passive balancing methods. By controlling the drive circuits of the Mosfets, the Mosfets is controlled in the amplifier mode and the energy can be discharged by the Mosfets with variable and controllable balancing current. The balancing circuits of the method is fabricated and the experimental validation is established. The experimental results verify that the proposed balancing method can realized the balancing function effectively and the balancing power can be high enough even without bleeder resistors